Genetically predicted body fat mass and distribution with diabetic kidney disease: A two-sample Mendelian randomization study - Wang, Min; Li, Xin; Mei, Hang; Huang, Zhao-Hui; Liu, Yue; Zhu, Yong-Hong; Ma, Tian-Kui; Fan, Qiu-Ling (Frontiers in Genetics, 2022)
The aim of this study is to apply a Mendelian randomization (MR) design to investigate the potential causal associations between the body mass index (BMI), body fat mass such as trunk fat mass and waist circumference (WC), and diabetic kidney disease (DKD). A two-sample MR study was conducted to obtain exposure and outcome data from previously published studies. The instrumental variables for BMI, trunk fat mass, and WC were selected from genome-wide association study datasets based on summary-level statistics. The random-effects inverse-variance weighted (IVW) method was used for the main analyses, and the weighted median and MR-Egger approaches were complementary. In total, three MR methods suggested that genetically predicted BMI, trunk fat mass, and WC were positively associated with DKD. Using IVW, we found evidence of causal relationships between BMI [odds ratio (OR) = 1.99; 95% confidence interval (CI), 1.47–2.69; p = 7.89 × 10−6], trunk fat mass (OR = 1.80; 95% CI, 1.28–2.53; p = 6.84 × 10−4), WC (OR = 2.48; 95% CI, 1.40–4.42; p = 1.93 × 10−3), and DKD. MR-Egger and weighted median regression also showed directionally similar estimates. Both funnel plots and MR-Egger intercepts showed no directional pleiotropic effects involving the aforementioned variables and DKD. Our MR analysis supported the causal effect of BMI, trunk fat mass, and WC on DKD. Individuals can substantially reduce DKD risk by reducing body fat mass and modifying their body fat distribution.